Understanding chronic inflammatory diseases in the human lung: the cystic fibrosis and idiopathic pulmonary fibrosis paradigms - Liu, Yi-Chia (2014)
The chronic infection of the cystic fibrosis (CF) lung with Pseudomonas aeruginosa strongly correlates with critical outcomes. Pseudomonas alkyl-quinolone signal (PQS) is a diffusible cell-density dependent signal controlling the production of virulence determinants. The PQS amount in the CF lung was proportionate to P. aeruginosa colonisation and PQS molecules have been demonstrated to inhibit pro-inflammatory signalling. However, how PQS influence the recognition of P. aeruginosa by the human lung is unknown. The contribution of PQS to the interaction of P. aeruginosa with human bronchial epithelial cells (HBECs) was characterised using a PQS-deficient mutant ΔpqsA in comparison with its isogenic wild type (WT). Although ΔpqsA appeared attenuated, the pathogenesis of WT and ΔpqsA upon infection of HBEC did not differ in bacterial growth, actin and junctional protein degradation, and pro-inflammatory activation. Despite PQS being highly secreted by a CF isolate LESB58, preliminary data showed that LESB58 was less cytotoxic than the laboratory WT. Our results suggest that PQS does not alter P. aeruginosa pathogenicity on HBECs.